A cross sectional study on pattern and associated risk factors of musculoskeletal morbidities among government bus drivers in Mangalore, Karnataka - ., Vinu; Premlal, K. S.; Nagalingam, Saranya (International Journal Of Community Medicine And Public Health, 2018)
Background: Absenteeism, turnover and disability among the drivers appeared to be high. The main conditions leading to disablement among drivers are related to cardiovascular diseases, psychological problems and musculo-skeletal disorders. This study was planned to determine the pattern of musculoskeletal morbidities among government bus drivers in Mangalore, the associated risk factors of musculoskeletal morbidities. Methods: A cross sectional study was conducted at Mangalore KSRTC Bus Depot among 310 bus drivers over a period of 18 months from 2014 to 2016 yr. The study was conducted in three depots of KSRTC division Mangalore in Mangalore city. Results: In our study all drivers were males, the mean age 44.88 years. Out of the 310 bus drivers who participated in the study 298 belonged to upper middle class indicating that the KSRTC drivers are financially stable. The common morbidities were musculoskeletal problems especially low back ache 84.8% followed by neck pain 46.8%,about 32.3% had shoulder pain 15.8% had knee joint involvement. The proportion of bus drivers with hypertension and diabetes mellitus was 35.8%and 7.7% respectively. Out of the 310 bus drivers 239 (77.1%) consumes alcohol. The prevalence of smoking was (85.5%) and tobacco chewing was 14.5%. Conclusions: During our study we found that there is an increased prevalence of chronic conditions like diabetes mellitus and hypertension, this is attributable to the increase stress faced by the drivers in terms of the responsibility they carry to transport the public of all age groups. This unnoticed stress plays a very important part in development of the chronic conditions.